Determinants of speech and language delay among children aged 12 months to 12 years at Yekatit 12 Hospital, Addis Ababa, Ethiopia: a case-control study - Feven Y. Moges; Zuriyash Mengistu; Sosina W. Tilahun (BMC, 2024)
Abstract Background Speech and language delay among children can result in social interaction problems, attention difficulties, decreased writing and reading abilities, and poor cognitive and behavioral development. Despite the mounting prevalence of speech and language delays in Ethiopia, there is a lack of literature addressing the factors contributing to this delay. Consequently, this study aims to identify determinants of speech and language delay among children aged 12 months to 12 years at Yekatit 12 Hospital in Addis Ababa, Ethiopia. Methods We conducted an institutional-based at Yekatit 12 Hospital, unmatched case-control study with 50 cases and 100 controls aged 12 months to 12 years. Interviewer-administered questionnaires were used to collect data from the parents or caregivers of the participating children. Epi Info v7 was used for sample calculation, and SPSS v26 was used for analysis. The chi-square test was performed to determine the relationship between speech and language delay and determining factors, which was then followed by logistic regression. The significant determining factors were identified based on the adjusted odds ratio (AOR), with a 95% CI and p-value (< 0.05). Results Case group constituted 23 males and 27 females, totaling 50 children. Upon completing the multivariate analysis, birth asphyxia [AOR = 4.58, 95CI (1.23-16.99)], bottle-feeding [AOR = 4.54, 95CI (1.29-16.04)], mother-child separation [AOR = 2.6, 95CI (1.05-6.43)], multilingual family [AOR = 2.31, 95CI (1.03-5.18)], and screen time greater than two hours [AOR = 3.06, 95CI (1.29-7.28)] were found to be statistically significant determinants of speech and language delay. Conclusions Our study found that birth asphyxia, bottle-feeding, mother-child separation, being from a multilingual family, and excessive screen time contribute significantly to speech and language delay. As a result, it is important to develop interventions that target these modifiable factors, while also ensuring that early diagnosis and treatment options are readily accessible.